(untitled) (Boletín Epidemiológico Semanal, 2023)
Introduction: mumps is a common disease, which continues to cause outbreaks even in well-vaccinated vaccinated populations. The objective is to describe the surveillance of mumps in Spain. We present the analysis of cases reported to RENAVE (National epidemiological surveillance network) between 2005 and 2022 and the results of the mumps microbiological surveillance programme (PVMP) of the CNM (National Center of Microbiology) between 2016 and 2021. The completion of the variables and the integration of laboratory information in the reported cases are analysed. Method: Sources: cases reported to RENAVE and cases and samples from the CNM’s PVMP. Cases are analysed by year, autonomous community, sex and age, type of case, vaccination and laboratory data. Annual and period rates are calculated. Samples and determinations are analysed for PVMP. Results: Three epidemic waves are described: 2005-2009, 2010-2014 and 2015-2020. Incidence was minimal in 2021, recovering slightly in 2022. Mumps mainly affects adolescents and young adults. 32% of cases are vaccinated with two doses. Only 48% of investigated cases are confirmed. Saliva has the best PCR positivity rate. Completion is adequate for sociodemographic variables, low for vaccination and very low for severity. Information on laboratory studies performed in CNM is generally, not reported to RENAVE. Conclusions: Mumps is a common disease that should be monitored. All information generated in surveillance activities should be integrated into a single system devoted for public health action.